2013
DOI: 10.1007/s00259-013-2342-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodihydroxyphenylalanine vs other radiopharmaceuticals for imaging neuroendocrine tumours according to their type

Abstract: 6-Fluoro-(18F)-L-3,4-dihydroxyphenylalanine (FDOPA) is an amino acid analogue for positron emission tomography (PET) imaging which has been registered since 2006 in several European Union (EU) countries and by several pharmaceutical firms. Neuroendocrine tumour (NET) imaging is part of its registered indications. NET functional imaging is a very competitive niche, competitors of FDOPA being two well-established radiopharmaceuticals for scintigraphy, 123I-metaiodobenzylguanidine (MIBG) and 111In-pentetreotide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 139 publications
(198 reference statements)
0
74
0
6
Order By: Relevance
“…The 18 FDG -PET/CT examination (fluorodeoxyglucose) is usually negative in well-differentiated NENs, mainly G1 NENs [92,93]. However, it has been demonstrated that collection of 18 FGD in neoplastic foci is a negative prognostic factor [90].…”
Section: F-fdgmentioning
confidence: 99%
“…The 18 FDG -PET/CT examination (fluorodeoxyglucose) is usually negative in well-differentiated NENs, mainly G1 NENs [92,93]. However, it has been demonstrated that collection of 18 FGD in neoplastic foci is a negative prognostic factor [90].…”
Section: F-fdgmentioning
confidence: 99%
“…This amino acid tracer visualizes those cells that possess the capability to take up the aromatic amino acid precursor and are involved in the biosynthesis of dopamine. 18 F-DOPA has been shown to be a good tracer for welldifferentiated neuroendocrine tumors originating from the gastrointestinal tract (1)(2)(3). In addition, 18 F-DOPA has also been shown to be a good tracer for other types of neuroendocrine tumors, such as neuroblastoma (4), medullary thyroid carcinoma, pheochromocytoma, and paraganglioma (1), and for malignancies of the central nervous system (5).…”
mentioning
confidence: 99%
“…18 F-DOPA has been shown to be a good tracer for welldifferentiated neuroendocrine tumors originating from the gastrointestinal tract (1)(2)(3). In addition, 18 F-DOPA has also been shown to be a good tracer for other types of neuroendocrine tumors, such as neuroblastoma (4), medullary thyroid carcinoma, pheochromocytoma, and paraganglioma (1), and for malignancies of the central nervous system (5). Finally, imaging dopamine metabolism in the central nervous system with 18 F-DOPA is an effective means to determine the extent of degeneration of presynaptic dopaminergic neurons in Parkinson disease (6).…”
mentioning
confidence: 99%
“…Therefore, in this clinical scenario, 18 F-DOPA has to be comparable to other radiopharmaceuticals used for imaging NETs, and the choice of the best one depends mainly on the most probable primary neoplasm and its aggressiveness. A recent review on this topic reported that, currently, 18 F-DOPA seems to have better diagnostic accuracy than other radiopharmaceuticals in some precise NET subtypes: medullary thyroid cancer, catecholamine-producing tumors with low aggressiveness, and well-differentiated carcinoid tumors of the midgut, as well as in congenital hyperinsulinism (17). Nevertheless, for correct image interpretation, it is mandatory that the interpreter be well aware of 18 F-DOPA physiologic biodistribution and normal variants, including possible pitfalls that may lead to PET/CT misinterpretations in various clinical settings (18).…”
Section: See Page 367mentioning
confidence: 99%